Spectrometric Study of the Nitrile-Ketenimine Tautomerism. (19th July 2009) - Saraví Cisneros, Hebe; Laurella, Sergio; Ruiz, Danila L.; Ponzinibbio, Agustín; Allegretti, Patricia E.; Furlong, Jorge J. P.
Abstract : Mass spectrometry is used to evaluate the occurrence of the nitrile-ketenimine tautomerism. Mass spectra of two differently substituted nitriles, ethyl-4, 4-dicyano-3-methyl-3-butenoate and diethyl-2-cyano-3-methyl-2-pentenodiate are examined looking for common mass spectral behaviors. Ion fragmentation assignments for specific tautomers allow to predict the presence of the corresponding structures. Additionally, the mass spectrum and nuclear magnetic resonance spectra of ethyl-4, 4-dicyano-2, 2-diethyl-3-methyl-3-butenoate and that of the corresponding amination product support the occurrence of the ketenimine tautomer in the equilibrium.